Revolutionary Premiere 6. - Darkin, Christian, ....-; Allen, Joe, ....-; Schaeffer, Mark, ....- (Birmingham : Friends of ED, 2001)
The Desktop Video Revolution is here! You won't have missed the fact that digital is taking over, but you'd be wrong if you thought that all that those 1s and 0s can do for you is make your pictures a little bit clearer and your soundtrack a bit crisper. Digital video gives you complete control over every frame of your production. You really can just drag and drop scenes, clips, still, music, anything you want, onto the versatile timeline where you compose your final video. And if you make a mistake, you just hit Undo. Digital video editing really can be that easy, and this book will take you from start to finish learning how to digitally edit using Adobe's premier league desktop video solution.
Keywords: Computerprogramma's.; Desktop publishing